Comparação entre a perimetria de frequencia duplicada matrix e o potencial visual evocado multifocal em pacientes normais, suspeitos e portadores de glaucoma de ângulo aberto - Kanadani, Fabio Nishimura [UNIFESP] (2013)
INTRODUCTION: The Ã¢Â€Âœgold-standardÃ¢Â€Â glaucoma functional evaluation is the standard automated perimetry (SAP), however, the value of SAP depends on the reliability of the patientÃ¢Â€Â™s responses and external factors. So, different Technologies have been developed for earlier functional detection in glaucoma patients. The frequency-doubling technology (FDT) is believed to detect glaucoma functional defects earlier than SAP. The multifocal VEP (mfVEP) is an objective test for functional evaluation. OBJECTIVE: To evaluate the sensitivity and specificity of FDT and mfVEP tests in normals, suspects and glaucomatous eyes. To compare the monocular and interocular mfVEP. METHODS: 95 eyes from 95 individuals (23 normals, 33 glaucoma suspects and 39 glaucomatous) were enrolled. All participants performed an full ophthalmic examination, followed by SAP, FDT and mfVEP tests. RESULTS: The AUC for MD and PSD was 0.756 and 0.761 for FDT, respectively; for mfVEP interocular was 0.564 and 0.512 for Signal and Alpha, respectively; for mfVEP monocular was 0.568 and 0.538 for Signal and Alpha, respectively. There was no difference between mfVEP monocular and interocular. CONCLUSIONS: There was a strong superiority of FDT in relation to mfVEP in glaucoma detection. In our study, the mfVEP was not capable to identify early functional glaucoma defects. There was no difference between monocular and interocular mfVEP. KEY-WORDS: Glaucoma, Standard automated perimetry, Frequencydoubling perimetry, Multifocal visual evoked potentials, Eletrophysiology.